1998
DOI: 10.1038/bjc.1998.172
|View full text |Cite
|
Sign up to set email alerts
|

Two Li-Fraumeni syndrome families with novel germline p53 mutations: loss of the wild-type p53 allele in only 50% of tumours

Abstract: Summary We describe two Li-Fraumeni syndrome families. Family A was remarkable for two early childhood cases of adrenocortical tumours, family B for a high incidence of many characteristic cancers, including a childhood case of choroid plexus tumour. Using direct sequencing, we analysed exons 5-9 of the p53 gene in constitutional DNA of individuals from both families and found two novel germline mutations in exon 5. In family A, we detected a point substitution in codon 138 (GCC to CCC), which resulted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
(16 reference statements)
2
16
0
Order By: Relevance
“…Analysis of tumors occurring in p53 heterozygous knockout mice demonstrate that a signi®cant proportion (*40%) retain the normal allele (Venkatachalam et al, 1998). These observations are recapitulated in tumors derived from LFS carriers with germline p53 mutations in which the normal allele is frequently retained in the cancer (Sedlacek et al, 1998;. It has been suggested that a reduction iǹ functional expression' of the normal allele leads to p53 inactivation, cell cycle dysregulation and malignant transformation (Dobbelstein and Roth, 1998).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Analysis of tumors occurring in p53 heterozygous knockout mice demonstrate that a signi®cant proportion (*40%) retain the normal allele (Venkatachalam et al, 1998). These observations are recapitulated in tumors derived from LFS carriers with germline p53 mutations in which the normal allele is frequently retained in the cancer (Sedlacek et al, 1998;. It has been suggested that a reduction iǹ functional expression' of the normal allele leads to p53 inactivation, cell cycle dysregulation and malignant transformation (Dobbelstein and Roth, 1998).…”
Section: Discussionmentioning
confidence: 67%
“…Approximately 50% of tumors that develop in LFS patients retain the normal p53 allele (Sedlacek et al, 1998;. However, the mechanism by which tumor formation occurs in these patients has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports in the literature for several tsg, namely Nf1 (Jacks et al, 1994), p27 Kip1 (Pietenpol et al, 1995), Msh2 (de Wind et al, 1998, Pten (Podsypanina et al, 1999), Tsc2 (Kobayashi et al, 1999), CBFA2 (Song et al, 1999) and p53 (Nigro et al, 1989;Mulligan et al, 1990;Davido et al, 1991;Sedlacek et al, 1998), of tumours retaining a single possibly active allele. But by far the strongest evidence of this kind is for haploinsu ciency of p53 and p27 Kip1 in hemizygous mice, where the potential complication of dominant negative mutations has been excluded (Venkatachalam et al, 1998;Fero et al, 1998).…”
mentioning
confidence: 99%
“…(3) Between these two extremes, there will be haploinsu cient tsg which are lost homozygously in some tumours and hemizygously in others, depending on the interactions between the stochastic occurrence of chromosomal lesions and other in¯uences on the physiology and growth of the individual emerging tumour. Examples are p53, loss of which could be as much as 50% hemizygous (Nigro et al, 1989;Mulligan et al, 1990;Davido et al, 1991;Sedlacek et al, 1998), and DCC, most often hemizygous (Cho et al, 1994). (4) With regard to familial cancer, germline tsg mutations conferring the strongest and earliestacting selective advantage will be most easily detected, regardless of haploinsu ciency.…”
mentioning
confidence: 99%